The bittersweet smell of success: Malicious online responses to others achievements - Hornik, Jacob; Ofir, Chezy; Rachamim, Matti; Grossman, Ori (Frontiers in Psychology, 2023)
A prominent recurring theme in social comparison is the concept that individuals are not indifferent to the results that others achieve, and typically seek pleasure while avoiding pain. However, in some cases they behave atypically–counter to this principle. The purpose of this research is to investigate one atypical response, namely gluckschmerz–a negative response to information about others’ success (feeling bad at others’ fortunes). To advance objectives, a mixed-mode of two studies were conducted using a combination of primary and secondary analyzes, and qualitative and quantitative methods. Findings reveal that this aversive feeling encourages consumers to share online “positive” information with others but using negative malicious word-of-mouth narratives. They provide compelling evidence supporting the theory that some of the positive commercial information conveyed through electronic media triggers negative word-of mouth in the form of online firestorms driven by the discordant atypical sentiment of gluckschmerz.